Abundance and diversity of beetles in Eucalyptus globulus in the Andean community of Viñas, Tayacaja, Huancavelica - Saldaña-Chafloque, Charles Frank (2023)
Objective: The study of the abundance and diversity of Coleoptera in Eucalyptus globulus plantations in the Andean Community of Viñas-Pampas, Tayacaja, Huancavelica. Methodology: Descriptive study, the 7 sampling units were randomly distributed, with transects comprised of 50m x 20m, where the number of species found was evaluated. The number of insects present in trees with DAP less than 10 cm was evaluated. Subsequently, we proceeded with the taxonomic identification. Results: 11 species were identified in the Viñas-Pampas annex, comprising the following families: Chrysomelidae (01), Curculionidae (05), Cerambycidae (01), Coccinellidae (01), Carabidae (02) and Lampyridae (01). While the most abundant species was Gonipterus platensis (41.68%). The most frequent species are Gonipterus platensis (20.59%) and Gonipterus scutellatus (20.59%). The Simpson Index (0.6797), Shannon - Wiener Index (1.4237) and Margalef Index (0.6420) are reported. Conclusions: According to the Simpson Index, it was demonstrated that there is dominance of some species, in this case mainly by Gonipterus platensis; the Shannon - Wiener Index and the Margalef Index indicate low species diversity.